BHUMI LENTERA WADAH MENGASAH POTENSI PASCA PANDEMI - Elma Aviani; Ranny Rahmawati; Septin Bilkhis Silviana; Ayu Pipih Lestari; Fergi Diarta (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Bhumi Lentera is a non-profit organization that focuses on education. Its goal is to provide learning assistance and help sharpen talents, that have been hindered by the Covid-19 pandemic. The activities are conducted for free on Sundays, with a focus on cognitive development in weeks 1 and 3, and talent development in weeks 2 and 4. Each activity consists of several stages, including planning, implementation, and evaluation, to ensure optimal execution and achievement of goals. The organization hopes that these activities can enhance the cognitive abilities and skills of the students involved, thereby reducing the knowledge gap caused by the Covid-19 pandemic that has limited traditional learning environments